PENGEMBANGAN SOFT SKILL BERBASIS KARIR PADA SMK DI KOTA SEMARANG - Utaminingsih, Sri (Dinamika Pendidikan, 2011)
The objectives of the study was to find and develop the soft skill learning model based careers on Vocational High School (SMK) with Tourism Cluster through a set of tryout and validation. The soft skill development based careers was expected to improve Vocational High Schoolsâ graduates and fulfill the qualifications which were set by BI (Business and Industry). It was relevant to the Presidentâs policy to improve Indonesian workers. The specific purposes of the study were: (1) to formulate the development of soft skill model design based careers on Vocational High School, (2) to find the soft skill development model based the effective careers on Vocational High Schools, (3) to compile the soft skill model guidance. This study used Research and Development approach, then continued to the field study process, developing the model design, tryout and finally, validation. At the introduction study, it was identified the values and soft skills supporting careers in business and industry. Then, those values became the foundation to (1) formulate the model design, and (2) compile the model develop the soft skills collaboratively involving the parties and stakeholders related to Vocational High Schools with Tourism Cluster, (3) create an effective model guidance. From the process of development above, it was obtained the model design and the soft skill development model guidance to improve the graduatesâ careers.